Existence of Solutions For Higher Order Impulsive Integro-Differential Equations With Antiperiodic Boundary Value Problems On Time Scales - D, Arunkumar; K, Kannan; K, Anitha; B, Sujatha; M G, Gnanavel (Journal of Neonatal Surgery, 2025)
In this paper, we investigate the higher order impulsive integro-differential equations with anti periodic boundary value problems on time scales. The Contraction mapping principle and Leray Schauder's fixed point theorem are used to determine sufficient conditions. Finally, we present an example to demonstrate the main results.